Evaluating the relationship between body-worn cameras and more acccountable or effective policing in South Africa : a critical examination of theory, policy, and practice from an international human rights law perspective - Probert, Thomas (University of Pretoria, 2023)
Thesis (PhD ( Freedom from Violence in Africa))--University of Pretoria, 2022.